Temperature Monitoring System for Egg Incubators Using Raspberry Pi3 Based on Internet of Things (IoT) - Siti Purwanti; Anita Febriani; Mardeni Mardeni; Yuda Irawan (Journal of Robotics and Control (JRC), 2021)
The incubator is made as a substitute for hatching naturally at the same time. The success of the hatch machine is largely determined by the temperature stability in the incubator. In the use of small-scale hatcheries for native chicken hatching, they are still faced with the problem of low hatchability due to one of the obstacles, namely the power outage during the hatching process. To improve the monitoring performance of egg incubators, the writer wishes to conduct research "Monitoring to Control and Monitor Temperature in Egg Incubators" using a webcam camera to monitor temperature conditions and hatch eggs. The working system is the DHT11 sensor will detect the temperature, the webcam camera in real time will monitor the state of the eggs then the raspberry pi3 will automatically control the temperature and electrical energy on the incubator, the smartphone monitors and can also control the temperature with the state of the eggs in realtime, 12V battery as a replacement energy when the PLN goes out. From the results of the tests carried out, the authors can draw conclusions, namely: The webcam camera can display the condition of the eggs in the incubator room. Android smartphones can receive information with a webcam camera during the hatching process. The data logger can display recapitulated temperature and humidity data.